Advances in hepatitis delta research: emerging insights and future directions - Degasperi, Elisabetta; Anolli, Maria Paola; Lampertico, Pietro (Sexually transmitted infections, 2024)
ObjectivesHepatitis delta virus (HDV) is a defective virus needing the envelope provided by hepatitis B virus (HBV) in order to enter liver cells and propagate. Chronic HDV infection is considered the most severe viral hepatitis, resulting in accelerated fibrosis progression until cirrhosis and its complications (hepatocellular carcinoma, liver decompensation) compared with HBV mono-infected patients. Off-label treatment with interferon has represented the only treatment option in the last 40 years, resulting in suboptimal virological response rates and being limited by safety issues especially in patients with advanced cirrhosis. Recently, the first HBV-HDV entry inhibitor Bulevirtide (BLV) has been approved by the European Medicines Agency (EMA) for treatment of chronic compensated HDV.MethodsThis review summarises most recent updates on HDV epidemiology, diagnosis and treatment, with a special focus both on clinical trials and real-life studies about BLV. An overview on new HDV compounds under development is also provided.ResultsBLV, the HBV-HDV entry inhibitor, has shown promising safety and efficacy data in clinical trials and in real-life studies, also in patients with advanced cirrhosis and portal hypertension. However, according to EMA label treatment is currently intended long-term until clinical benefit and predictors of responses are still undefined. The potential combination with PegIFNα seems to increase virological and clinical responses. New compounds are under development or in pipeline for treatment of HDV.ConclusionAfter more than 40 years since HDV discovery, new treatment options are currently available to provide efficient strategies for chronic hepatitis Delta.